PELAYANAN KONTEKSTUAL RASUL PAULUS DITINJAU DARI 1 KORINTUS 9:19-23 - ardianus hulu (STT BIBLIKA JAKARTA, 2021)
This research is intended to find out what are the principles of contextual ministry carried out by the apostle Paul based on 1 Corinthians 9:19-22. This research was conducted using a qualitative method with a literature study using inductive biblical interpretation (execution), then searching for other sources. that supports it. The discussion shows that there are conditions for doing contextual service, then there is a contextual service strategy, then there is ethics in contextual service as well as the purpose of contextual service now.